A argumentação de alunos de ensino médio em aula de Física: o tema energia elétrica e fontes de energia - Kawazoe, Elisabete Favoretto (2009)
The current essay presents a study on 3rd grade high school students' argumentative due forms when having Physics classes, after having read about the theme Electrical Energy by means of texts of science history and practical activities involving the subject, energetic sources and its environmental implications. Methodologically, it was used a qualitative approach. We established our studies on Chaim Perelman and Olbrechts-Tyteca (2005), George Lakoff and Mark Johnson (2002), Oliver Reboul (2004), Philiipe Breton (2003) and Martin Bauer and George Gaskell (2002). We analysed: a) the rethorical resources of Dufay and Franklin's historical texts to measure the range of their argumentation referring to communication of the theme electricity; we examined the present rhetorical illustrations on the teacher and students' argumentation in the established argumentative dynamic among them after their reading of Dufay and Franklin's texts ; c) the practical activities which were recorded on 30 July 2008 and 12 August 2008, for the matter of persuasive and cognitive implications related to the analysed phenomena. We obtained the following results: a) The students participated actively of the developed practices and elaborated explanations about the studied phenomena; b) the enlargement of the power of arguing, countering, criticize and reflect about different views.